Antibacterial potential of nudibranch-associated bacteria from Saparua and Nusa Laut Islands, Indonesia - RHESI KRISTIANA; MADA TRIANDALA SIBERO; MACELLYNE YOHANNA FARISA; DIAH AYUNINGRUM; DIO DIRGANTARA; MUHAMMAD HANAFI; OCKY KARNA RADJASA; AGUS SABDONO; AGUS TRIANTO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Kristiana R, Sibero MT, Farisa MY, Ayuningrum D, Dirgantara D, Hanafi M, Radjasa OK, Sabdono A, Trianto A. 2019. Antibacterial potential of nudibranch-associated bacteria from Saparua and Nusa Laut Islands, Indonesia. Biodiversitas 20: 1811-1819. Infections caused by multidrug-resistant bacteria are the international health issue that triggers the urgency of finding new antibacterial agents. The aim of this study was to obtain the nudibranchs-associated bacteria that have bioactivity against multidrug-resistant bacteria. A total of 13 species of nudibranch were identified based on morphological characterization. Overlay methods were used for the screening of the isolates bioactivity against six pathogenic multidrug-resistant bacteria. The Minimum Inhibition Concentration (MIC) of the crude extract was evaluated against Methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli, Bacillus subtilis, Klebsiella pneumonia, Micrococcus luteus, and Extended Spectrum Beta Lactamases E. coli (ESBL) using MTT method. A total of 145 isolates were obtained which eleven of the isolates showed antibacterial activity against the pathogenic bacteria. The MIC tests showed that the best acivity was isolate SM-S-9-15 and SM-N-3-7. The methanolic extract of isolate SM-S-9-15 active to all of the pathogenic bacteria, while the ethyl acetate extract of the isolate SM-N-3-7 active to the E. coli, B. subtilis, K. pneumonia at the concentration of 500 mg/mL. According to 16S ribosomal RNA gene sequence-based identification, all active isolates belong to Virgibacillus marismortui, V. dokdonensis, Bacillus kochii, Vibrio algynoliticus, and Pseudoalteromonas piscicida.